2
$\begingroup$

So the question is basically z transform the given system.

$(y[n+2] + 3y[n+1] - 4y[n])=(x[n+2] - 5x[n+1])$

I've to find h[z] first then it's really easy to solve it. So that's what I got so far;

$z^2y(z) + 3zy(z) - 4y(z) = z^2x(z) - 5zx(z)$

$(z^2+3z-4)y(z) = (z^2 - 5z)x(z)$

$H(z) = \frac{y(z)}{x(z)} = \frac{z^2-5z}{z^2+3z-4}$

then

$H(z) = 1 - \frac{4}{5(z-1)}-\frac{36}{5(z+4)}$

I've to find Z transform pair but I'm stuck here. Thanks in advance!

Here is the z transform table from schaums;

table

$\endgroup$
  • $\begingroup$ $z^2+3z-4 = (z-1)(z+4)$ then partial fractions $\endgroup$ – G Cab Jan 13 at 18:08
  • $\begingroup$ I've updated the question. I tried every way to simplify this. Can you check it out? @GCab $\endgroup$ – L4W Jan 13 at 18:17
  • $\begingroup$ Are you studying bilateral $Z$ transform ($z$ ranges from $-\infty$ to $\infty$)? $\endgroup$ – Shubham Johri Jan 13 at 18:34
0
$\begingroup$

Using $H(z)=\frac{z^2-5z}{(z+4)(z-1)}=\frac{Az}{z-1}+\frac{Bz}{z+4}+C$ we get $A=-4/5,B=9/5,C=0$. Can you complete?

From your list we see that $Z[-a^nu[-1-n]]=\frac z{z-a}$ and thus$$Z[-u[-1-n]]=\frac z{z-1}\\Z[-(-4)^nu[-1-n]]=\frac z{z+4}$$Thus, by the linearity of the inverse $Z$ transform, we get$$Z^{-1}[H(z)]=AZ^{-1}[z/(z-1)]+BZ^{-1}[z(z+4)]\\=\frac45u[-1-n]-\frac95(-4)^nu[-1-n]$$

$\endgroup$
  • $\begingroup$ Can you help me out finding the solution please. I know I'm asking too much :( $\endgroup$ – L4W Jan 13 at 18:38
  • $\begingroup$ @L4W Look at the spoiler in my answer $\endgroup$ – Shubham Johri Jan 13 at 18:44
  • $\begingroup$ Thanks a lot, couldn't find out without you! $\endgroup$ – L4W Jan 13 at 18:46
  • $\begingroup$ You are welcome ;) $\endgroup$ – Shubham Johri Jan 13 at 18:46
  • $\begingroup$ By the way isn't $C = 1$ $\endgroup$ – L4W Jan 13 at 18:47

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.